You are on page 1of 18

Semigroups of Operators in Banach Space

We begin with a definition
Definition 1. A one-parameter family T (t) for 0 ≤ t < ∞ of bounded linear operators on a Banach
space X is a C0 (or strongly continuous) Semigroup on X if
1. T (0) = I (the identity on X).
2. T (t + s) = T (t)T (s) (semigroup property)
3. lim T (t)v = v for all v ∈ X (This the Strong Continuity at t = 0, i.e., continuous at t = 0 in
t↓0

the strong operator topology).
Theorem 1. If T (t) is a C0 semigroup, then there exists ω ≥ 0 and M ≥ 1 such that
kT (t)k ≤ M eωt

t ≥ 0.

(1)

Proof:
1. First we show that kT (t)k is bounded on 0 ≤ t ≤ η for some η > 0.
If not then there exist {tn } such that tn ↓ 0 and kT (tn )k ≥ n. From the principle of uniform
boundedness there must exist a v ∈ X such that kT (tn )vk is unbounded. But this contradicts
the strong continuity at t = 0. Thus there exists η and M such that kT(t)k ≤ M for 0 ≤ t ≤ η.
Also since kT (0)k = 1 we must have M ≥ 1.
2. Let
ω=

ln(M )
.
η

Given any t ≥ 0 there exists n ∈ Z and δ with 0 ≤ δ ≤ η so that t = nη + δ. Then by the
semigroup property we have
kT(t)k = kT (δ)T (η)n k ≤ M n+1 .
3. Now t = nη + δ implies
n=

(t − δ)
t

η
η

and since M ≥ 1 we have 

kT(t)k ≤ M M n ≤ M M t/η .
Now ω = ln(M )/η implies ln(M ) = ηω which implies M = eωη . Thus we have  

t/η
kT(t)k ≤ M M t/η = M eωη
= M eωt .

1

Proof: Let t > 0. (5) d T (t)v = AT (t)v = T (t)Av. dt (6) A 0 (c) for every v ∈ D(A). 2 Definition 2. ∞) into X. 0 Z t  T (s)v ds = T (t)v − v. Then we have (a) for v ∈ X 1 lim h→0 h Z Z t+h T (s)v ds = T (t)v (4) t t T (s)v ds ∈ D(A) and (b) For every v ∈ X. s Proof: 2 t (7) . T (t)v ∈ D(A) and (d) for every v ∈ D(A). T (t)v is continuous on R0+ = [0. Similarly we have kT (t − h)v − T (t)vk ≤ kT (t − h)kkv − T (h)vk h→0 ≤ M eωt kv − T (h)vk −−→ 0.2 Corollary 1. h ≥ 0 and v ∈ X. Let T (t) be a C0 semigroup and A its infinitesimal generator . The Infinitesimal Generator of T (t) is the linear operator A defined as follows   T (t)v − v D(A) = v ∈ X : lim exists (2) t→0 t and for v ∈ D(A) we define T (t)v − v . then we have kT (t + h)v − T (t)vk ≤ kT (t)kkT (h)v − vk h→0 ≤ M eωt kT (h)v − vk −−→ 0 for t ≥ h ≥ 0 due to strong continuity at h = 0. Z T (t)v − T (s)v = t Z T (τ )Av dτ = s AT (τ )v dτ. t→0 t Av = lim (3) Theorem 2. If T (t) is a C0 semigroup then for every v ∈ X.

Thus we conclude that T (t)v ∈ D(A) and AT (t)v = T (t)Av. h↓0 h dt 3 . s∈[t.t+h] (b) For part (b) let v ∈ X and h > 0. For any fixed t > 0 with 0 < h < t we show the following limit exists.  Z t   T (h) − I T (s)v ds . Z t+h Z t+h 1 1 T (s)v ds − T (t)v = [T (s)v − T (t)v] ds h h t t (8) h→0 ≤ sup kT (s)v − T (t)vk −−→ 0.(a) To prove part (a) we use the continuity of T (t)v. then     T (h) − I T (h) − I h→0 (T (t)v) = T (t) v −−→ T (t)Av h h (9) since v ∈ D(A). But we note that the limit in (9) only shows that T (t + h) − T (t) d+ lim v= T (t)v. So the limit exists which implies that 0 D(A) and (by the definition of A)  Z t T (s)v ds = (T (t)v − v). A 0 (c) As for part (c) we let v ∈ D(A) and h > 0. lim h→0 h 0 To this end we note that   Z t  T (h) − I T (s)v ds h 0 = = = = = Z 1 t (T (s + h)v − T (s)v) ds h 0 Z Z 1 t 1 t T (s + h)v ds − T (s)v ds h 0 h 0 Z Z 1 t+h 1 t T (s)v ds − T (s)v ds h h h 0 Z h Z t  Z Z 1 t+h 1 t 1 T (s)v ds + T (s)v ds − + T (s)v ds h t h h h 0 h Z Z 1 t+h 1 h T (s)v ds − T (s)v ds h t h 0 h→0 −−→ (T (t)v − v) Z t T (s)v ds ∈ where on the last step we have used part (a).

then D(A) is dense in X and A is a closed linear operator. in the first term we have used the fact that kT (t − h)k is bounded and v ∈ D(A). Proof: For any v ∈ X set 1 vt = t t Z T (s)v ds. t] is uniformly bounded for any fixed t > 0 which implies T (s)Avn → T (s)w uniformly for s ∈ [0. To this end we take {vn } ⊂ D(A) such that vn → v and Avn → w. If A is the infinitesimal generator of a C0 semigroup T (t). t]. 2 Corollary 2. 0 By Part (b) of Theorem 2. dt    T (t)v − T (t − h)v T (t)v − T (t − h)v lim − T (t)Av = lim h↓0 h↓0 h h To show that  − T (t − h)v + T (t − h)v − T (t)Av   T (h)v − v = lim T (t − h) − Av h↓0 h + lim (T (t − h)Av − T (t)Av) h↓0 =0+0=0 where on the last step. By part (d) of Theorem 2 we have Z t T (s)Avn ds. In the second term we used the strong continuity of T (t). vt ∈ D(A) for every t > 0 and by part (a) we have vt → v as t ↓ 0. Also the limit on the left exists and we have 0 Z T (t)v − v = T (s)v ds 0 4 t .d T (t)v exists we fix t > 0 and consider the left derivative. (d) To establish part (d) we simply integrate the result from part (c). Namely we have n→∞ kT (s)Avn − T (s)wk ≤ kT (s)kkAvn − wk −−−→ 0 uniformly in s in a compact set. T (t)vn − vn = (10) 0 By (1) we have that T (s) for s ∈ [0. The linearity of A is obvious so we only need to show that A is closed. This implies that the right hand side in (10) converges to Z t T (s)w ds.

for any δ > w0 there exists a t0 such that w(t0 ) <δ t0 5 . 1. If w is sub-additive and bounded above on any finite subinterval. A function w : R+ → R is called sub-additive if w(t1 + t2 ) ≤ w(t1 ) + w(t2 ). or − ∞. Definition 3. t→∞ t w0 = lim Proof: Since w(t) is bounded above on any finite t interval. Let T (t) and S(t) be two C0 semigroups with infinitesimal generator A and B respectively. then w(t) t>0 t w0 = inf and is finite. t>0 t 2 (11) 2. 0 By part (a) of Theorem 2 the limit on the right exists and goes to w. T (t)v = S(t)v But the D(A) = D(B) is dense by Corollary 2 so T (t) = S(t) for all t. Lemma 1. If A = B then T (t) = S(t) for all t. Theorem 3. where on the last step we have used the assumption that A = B. This implies that [T (t − s)S(s)] v is a constant. Then from Theorem 2 part (c) we have that the map s 7→ T (t − s)S(s)v is differentiable and d [T (t − s)S(s)] v = −AT (t − s)S(s)v + T (t − s)BS(s)v ds = −T (t − s)AS(s)v + T (t − s)BS(s)v = 0. The growth bound of a C0 semigroup T (t) is defined to be   ln(kT (t)k ω0 = inf . Thus we see that v ∈ D(A) 2 and Av = w. Proof: Let v ∈ D(A) = D(B). We set first s = 0 and then s = t to obtain ∀ v ∈ D(A) = D(B).which implies 1 T (t)v − v = t t Z t T (s)v ds. w(t) .

Proof: Let w(t) = ln(kT(t)k). for all t ≥ 0 kT(t)k ≤ Mω eωt . t w(t) t>0 t w0 = inf we must also have w0 ≤ lim inf t→∞ Thus we have lim sup t→∞ and therefore w(t) . Now for any t > 0 we can write t = nt0 + r with n ∈ Z and 0 ≤ r ≤ t0 .(by definition of the infimum and the fact that δ > w0 ). t t0 Since this holds for every δ > w0 we have lim sup t→∞ But since w(t) ≤ w0 . Then w(t1 + t2 ) = ln(kT (t1 + t2 )k) = ln(kT (t1 )T (t2 )k) ≤ ln(kT (t1 )kkT (t2 )k) = ln(kT (t1 )k) + ln(kT (t2 )k) = w(t1 ) + w(t2 ). t→∞ t (12) and for every ω > ω0 there exists a Mω such that. t w(t) w(t) ≤ w0 ≤ lim inf . Theorem 4. t→∞ t t w(t) . If T (t) is a C0 semigroup in X the the growth bound ω0 is given by   ln(kT (t)k ω0 = lim . t→∞ t w0 = lim 2 The above all works even if w0 = −∞. 6 (13) . Then we have w(t) w(nt0 + r) w(nt0 ) + w(r) = ≤ t t t nw(t0 ) + w(r) nw(t0 ) w(r) ≤ = + t nt0 + r t w(t0 ) w(r) w(t0 ) w(r) = + ≤ + t0 + r/n t t0 t which implies that lim sup t→∞ w(t0 ) w(t) ≤ < δ.

. Thus we can apply Lemma 1 to obtain ln(M ) ln(kT(t)k) ≤ lim + ω. Definition 4. 7 (14) . t0 ]. we have kT(t)k ≤ Mω eωt ∀ t ≥ 0. that there exists a M0 so that kT(t)k ≤ M0 Let Then for 0 ≤ t ≤ t0 . since kT (t)k is continuous on the closed bounded set [0. Throughout the remainder of these notes we use the notation Rλ = (λ − A)−1 to denote the resolvent operator for λ ∈ ρ(A). ∀ t ≥ 0 if ω < 0. . We want to show that there exists a Mω such that for all t ≥ 0 kT(t)k ≤ Mω eωt . Now consider 0 ≤ t ≤ t0 . 2 Remark 1. We already know. We also can see that it is bounded above since by (1) w(t) = ln(kT(t)k) ≤ ln(M eωt ) ≤ ln(M ) + ωt ∀t > 0. It is important to note that the growth bound ω0 . ( M0 Mω = e−ωt0 M0 ( M0 eωt kT(t)k ≤ (M0 e−ωt0 ) eωt if ω ≥ 0. unlike the constant ω given in (1) of Theorem 1. ∀ t ≥ 0 if ω ≥ 0. can be negative. Finally.so that w(t) is sub-additive. Notice that this implies kT(t)k ≤ eωt for t > t0 . t→∞ t→∞ t t ω0 = lim So we have ω0 ≤ ω. if ω < 0. Now we take any ω > ω0 . By the first part of the proof we see that if ω > ω0 then there exists a t0 > 0 such that ln(kT(t)k) <ω t for t > t0 . When ω0 is negative we say that the semigroup is exponentially stable since kT(t)k → 0 t → ∞.

Let Re (λ) > ω > ω0 . (σ − ω) We now show that e ∈ D(A) for all v ∈ X (i) Rv e = v for all v ∈ X and for all v ∈ D(A). (ii) (λ − A)Rv e = Rλ . 0 Then −λt e T (t)v ≤ Mω e(ω−σ)t kvk. s→0 (17) . R(λ e − A)v = v. If T (t) is a C0 semigroup in X with growth bound ω0 . so Z e ≤ kRvk ∞ −σt e Z kT (t)vk dt ≤ Mω ∞ (ω−σ)t e 0  dt kvk = 0 So we have e ≤ kRk Mω kvk (σ − ω) Mω . We show that e lim I1 = λRv s→0 and 8 lim I2 = v. Then λ ∈ ρ(A) and for every v ∈ X Z ∞ Rλ v = e−λt T (t)v dt (15) 0 and kRλ k ≤ Proof: Let Z e = Rv Mω (σ − ω) where σ = Re (λ). (16) ∞ e−λt T (t)v dt for v ∈ X σ = Re (λ) > ω. This will show that R To establish (i) we consider the limit   Z T (s) − I e 1 ∞ −λt Rv = e [T (s + t) − T (t)]v dt s s 0  Z ∞ Z ∞ 1 −λt −λ(t−s) e T (t)v dt e T (t)v dt − = s s 0   Z Z ∞ 1 λs ∞ −λt −λt = e T (t)v dt e e T (t)v dt − s 0 s   Z Z s Z ∞ 1 λs ∞ −λt λs −λt −λt = e e T (t)v dt − e e T (t)v dt − e T (t)v dt s 0 0 0 Z Z eλs − 1 ∞ −λt eλs s −λt = e T (t)v dt − e T (t)v dt s s 0 0 Z eλs − 1 e eλs s −λt = Rv − e T (t)v dt s s 0 ≡ I1 + I2 .Theorem 5.

in fact. Here we used the previous result that ARv Theorem 6. R(λ = λRv 2 e = λRv e − v. Or. α > ω. On the other hand.The first limit is trivial since it just gives the derivative of eλs . α−ω (18) then lim αRα v = lim α(α − A)−1 v = v α→∞ α→∞ 9 ∀ v ∈ X. For the second we note that Z 1 s v= v dt s 0 so we have Z s s→0  λ(s−t)  1 ≤ sup eλ(s−t) T (t)v − v − e T (t)v − v dt −→ 0. Since the limit on the right hand side in (17) exists we see that Rv e = λRv e − v. for every t we have  Z t Z t −λτ e T (τ )v dτ = e−λτ AT (τ )v dτ A 0 which implies Z 0 ∞ −λτ e A  T (τ )v dτ Z ∞ = 0 e−λτ AT (τ )v dτ 0 So for v ∈ D(A) we have e − A)v = λRv e − RAv e e − ARv e = λRv e − (λRv e − v) = v. ARv e =v (λ − A)Rv ∀ v ∈ X.s] e ∈ D(A) and. s 0 t∈[0. If A is a closed densely defined operator such that for every α > ω kRα k ≤ Mω . (19) . in other words. A 0 0 Therefore. for v ∈ D(A) we have Z ∞ e RAv = e−λτ T (τ )Av dτ Z0 ∞ e−λτ AT (τ )v dτ = 0  Z ∞ −λτ e T (τ )v dτ =A 0 e = ARv where we have used Theorem 2 part (c) and then parts (b) and (d) with s = 0 and arbitrary t which gives  Z t Z t −λτ e T (τ )v dτ = T (t)v − v = e−λτ AT (τ )v dτ.

 Then for all α > α00 we have kRα k ≤ Now choose α02 such that Mω  Mω < < 1 . choose α01 so large that (α01 − ω) > kAv kM . Since the D(A) is dense. for every  > 0 there exists a v ∈ D(A) such that kv − v k < . α−ω α0 − ω kAv k . and v ∈ X.Proof: Take α > ω. (20) For a fixed but arbitrary  > 0.

.

.

α .

2 .

.

.

α − ω .

α02 ). ≤ 2 ∀ α > α0 . Then we have kαRα v − vk = kαRα v −αRα v + αRα v −v + v −vk | {z } | {z } ≤ kαRα (v − v )k + kARα v k + kv − vk = kαRα (v − v )k + kRα Av k + kv − vk . (21) (22) Let α0 = max(α01 .

.

.

αMω .

.

kv − v k + kRα kkAv k + kv − vk .

≤.

α − ω.

Theorem 7 (Hille-Yoshida). On the fifth step we used (20). Since  is arbitrary we see that lim kαRα v − vk = 0. α→∞ 2 The next theorem is one of the most important results in semigroup theory. where on the first step we have added and subtracted αRα v and v . (21) and (22). It gives a complete characterization of the linear operators that can be the infinitesimal generator of a C0 semigroup. ≤ 2Mω +  +  = 2(Mω + 1). A linear operator A acting in a Banach space X is the infinitesimal generator of a C0 semigroup T (t) such that kT(t)k ≤ M eωt if. and only if (1) A is closed and D(A) = X 10 .

2 dα dα Continuing we find d(n−1) Rα v = (−1)(n−1) (n − 1)! Rαn v. From Corollary 2 we know that the infinitesimal generator is a densely defined closed operator. 3. in general. λ > ω. (23) Rα v = e−αt T (t)v dt and kRα k ≤ (α − ω) 0 Also. Then from Theorem 5 we also know that there is a ω0 such that for α > ω > ω0 implies α ∈ ρ(A). by the resolvent identity we have Rα+h (A) − Rα = −R(α)R(α + h). (α + h) − α Clearly we can pass to the limit as h goes to zero on the right side which means the limit on the left side exists and we have d Rα+h (A) − Rα Rα v = lim = lim −R(α)R(α + h) = −Rα2 v.(2) kRλn k ≤ M . 2. (n−1) dα But by (23) we have d d Rα v = dα dα Z ∞ −αt e Z T (t)v dt = (−1) 0 ∞ te−αt T (t)v dt 0 which implies d2 Rα v = (−1)2 dα2 ∞ Z t2 e−αt T (t)v dt 0 and. and Z ∞ Mω . (λ − ω)n n = 1. · · · . Proof: (⇒) Assume that T (t) is a C0 semigroup with infinitesimal generator A. h→0 (α + h) − α h→0 dα Thus we have d Rα v = −Rα2 v dα We can use the same argument together with the product rule to conclude that d2 d Rα v = −2Rα Rα v = (−1)2 2Rα3 v. 0 11 . d(n−1) Rα v = (−1)(n−1) dα(n−1) Z ∞ t(n−1) e−αt T (t)v dt 0 Combining these results we have (n − 1)! Rαn v Z = ∞ t(n−1) e−αt T (t)v dt.

Now by our assumption α > ω implies α ∈ ρ(A) which implies Aα ∈ B(X). a C0 semigroup. (λ − ω)n λ > ω. since Γ(n) = (n − 1)!. 2. By an exercise from the final take home exam we then see that Aα is the infinitesimal generator of a uniformly continuous 12 . · · · . (24) We need to address three points: (i) We need to show that “exp(At)” makes sense. (α − ω)n (⇐) Assume that A is a closed densely defined operator and there exists ω ∈ R. we have kRαn vk ≤ Mω kvk (α − ω)n which implies kRαn k ≤ Mω . (iii) show that the infinitesimal generator is A. To make sense of exp(At) we proceed using the so-called Yoshida Approximation Aα = αARα = α2 Rα − αI α ∈ ρ(A). Mω ≥ 1 such that for all α > ω implies α ∈ ρ(A) and kRλn k ≤ M . in turn. n = 1. (ii) show that this is.Thus we can obtain the following estimates Z ∞ n t(n−1) e−αt kT (t)vk dt. k(n − 1)! Rα vk ≤ 0 Z ∞ t(n−1) e−(α−ω)t dt ≤ Mω kvk 0 set u = (α − ω)t ⇒ du = (α − ω)dt n−1 Z ∞ u du = Mω kvk eu α−ω (α − ω) 0 Z ∞ Mω kvk = un−1 eu du n (α − ω) 0 Mω kvkΓ(n) = (α − ω)n Then. (25) We note that αRα − I = ARα since (αI − A)Rα = I. 3.

We show that there exists a C0 semigroup T (t) = lim Tα (t) α→∞ and that the infinitesimal generator is A. for v ∈ D(A). ARα v = Rα Av then Aα v = α2 Rα v − αv = αRα Av and we have lim (Aα v − Av) = lim (αRα (Av) − (Av)) = 0 α→∞ α→∞ by Theorem 6. 13 (28) . So we have Aα v → Av for all v ∈ D(A). (27) By our hypothesis (2) we can write ∞ X (α2 t)n −αt kTα (t)k ≤ e n! n=0 ∞ X (α2 t)n ≤ e−αt n! n=0 ∞ X =≤ Mω e−αt −αt = Mω e kRαn (A)k Mω (α − ω)n (α2 t)n (α − ω)n n! n=0 (α2 /(α−ω))t e = Mω e(αω/(α−ω))t . So for v ∈ D(A) we have. Thus Tα (t) is uniformly bounded on every compact t interval. From Theorem 6 we have αRα v → v ∀ v ∈ X.semigroup : Tα (t) = eAα t (α2 R =e (26) α −αI)t 2 = e−αt eα Rα t ∞ X (α2 t)n n Rα = e−αt n! n=0 where on the third step we used the fact that AB = BA ⇔ eA+B = eA eB and we have also used other results from the take home final concerning uniformly continuous semigroups. from (25) and.

(30) . (29) Using the power series representation for Tβ (T ) and (29) we have Aα Tβ (t) = Tβ (t)Aα . Now we also notice that Aα Aβ = (α2 Rα − α)(β 2 Rβ − β) = α2 β 2 Rα Rβ − α2 βRα − αβ 2 Rβ − αβI = α2 β 2 Rβ Rα − α2 βRα − αβ 2 Rβ − αβI = (β 2 Rβ − β)(α2 Rα − α) = A β Aα so that Aα A β = A β Aα . Rα Rβ = Rβ Rα .From the resolvent Identity Rα Rβ = Rβ − Rα = Rβ Rα α−β so that. in particular.

t Tα (t)v − Tβ (t)v = (Tβ (t − s)Tα (s)v).

(α − ω) (α − ω) We now show that α ≤ 2. 0  Claim 1. = (31) So for v ∈ D(A) we have 0 So we have t Z Tα (t)v − Tβ (t)v = Tβ (t − s)Tα (s) [Aα − Aβ ] v ds. (α − ω) 14 (32) . If α > 2|ω| > 0 then αω (α − ω)  < 2|ω|.0 Z t d (Tβ (t − s)Tα (s)v) ds = 0 ds Z t = [−Tβ (t − s)Aβ Tα (s) + Tβ (t − s)Aα Tα (s)] v ds 0 Z t (30) Tβ (t − s) [Aα − Aβ ] Tα (s)v ds = 0 Z t (30) Tβ (t − s)Tα (s) [Aα − Aβ ] v ds. Proof of Claim: α > 0 implies αω ≤ α|ω| and α > ω implies αω α|ω| ≤ .

(33) and for α. 15 (36) . β > 2|ω| we have. ∀ v ∈ D(A). Thus. the collection {Tα (t)v}α (for α tending to infinity ) is Cauchy in X and so it converges to an element of X which we denote by T (t)v: T (t)v = lim Tα (t)v. v ∈ X and  > 0. ∀ v ∈ X α→∞ and the limit is uniform on any compact t interval. 2 We conclude that T (t)v = lim Tα (t)v. implies there is a v0 ∈ D(A) such that kv − v0 k <  . α→∞ (35) Now for fixed t > 0. for v ∈ D(A). the denseness of D(A). for every t ≥ 0. β → ∞ (34) by (27). β large enough that  kTα (t)v0 − Tβ (t)v0 k < .To this end we note that α > 2|ω| ⇒ α > 2ω ⇒ −α < −2ω ⇒ α < −2ω + 2α = 2(α − ω) and dividing by (α − ω) in the last inequality gives the desired result. 4Mω e2|ω|t Therefore we have kTα (t)v − Tβ (t)vk ≤ kTα (t)v − Tα (t)v0 k + kTα (t)v0 − Tβ (t)v0 k + kTβ (t)v0 − Tβ (t)vk ≤ 2Mω e2|ω|t kv − v0 k + kTα (t)v0 − Tβ (t)v0 k   ≤ + = 2 2 provided we choose α. from (31) Z t   kTα (t)v − Tβ (t)vk ≤ Mω e2|ω|(t−s) Mω e2|ω|s k(Aα − Aβ )vk ds 0 Z t 2 2|ω|t ds k(Aα − Aβ )vk = Mω e 0 = Mω2 e2|ω|t t k(Aα − Aβ )vk ≤ Mω2 e2|ω|t t {kAα v − Avk + kAv − Aβ vk} → 0 as α. 2 From (28) and Claim 1 we have kTα (t)k ≤ Mω e2|ω|t .

T (t + s)v = T (t)T (s)v Proof: First we note that T (t + s)v = lim Tα (t + s)v = lim Tα (t)Tα (s)v. Therefore kT (t)k ≤ Mω eωt . kT (t + s)v − T (t)T (s)vk ≤ kT (t + s)v − Tα (t + s)vk + kTα (t + s)v − T (t)T (s)vk = kT (t + s)v − Tα (t + s)vk + kTα (t)Tα (s)v − T (t)T (s)vk → 0 as α → ∞.We also have kT (t)vk = lim kTα (t)vk α→∞ = lim inf kTα (t)vk α→∞ ≤ lim inf Mω e(αω/(α−ω))t kvk = α→∞ Mω eωt kvk. (ii) Now we show that T (0) = I. α→∞ α→∞ Next we note that kTα (t)Tα (s)v − T (t)T (s)vk = kTα (t)Tα (s)v − Tα (t)T (s)v + Tα (t)T (s)v − T (t)T (s)vk ≤ kTα (t)[Tα (s)v − T (s)v]k + k[Tα (t) − T (t)]T (s)vk ≤ kTα (t)kkTα (s)v − T (s)vk + kT (s)kkTα (t)v − T (t)vk ≤ Mω e2|ω|t kTα (s)v − T (s)vk + Mω e2|ω|s kTα (t)v − T (t)vk → 0 as α → ∞.e. (37) We now show that T (t) is a Strongly Continuous semigroup (i. 2 The claim is verified.. Claim 2. We have T (0)v = lim Tα (0)v = v. it is a C0 semigroup). (i) First we establish the semigroup property. α→∞ 16 .

First we show A ⊂ A.e.. for any fixed (finite δ). kTα (t)Aα v − T (t)Avk ≤ kTα (t)Aα v − Tα (t)Avk + kTα (t)Av − T (t)Avk ≤ kTα (t)kkAα v − Avk + k[Tα (t) − T (t)](Av)k ≤ Mω e2|ω|t kAα v − Avk + k[Tα (t) − T (t)](Av)k → 0 as α → ∞ and the convergence is uniform on compact t intervals. i. Thus we have kT (t)v − vk ≤  for t < δ0 . i.. Then we Therefore T (t) is a C0 semigroup. Since Tα0 (t) is strongly continuous there exists a δ0 < δ such that kTα0 (t)v − vk ≤  2 for t < δ0 . δ]. 0 17 .(iii) Next we show the continuity at t = 0. t→0 We have t→0 kT (t)v − vk ≤ kT (t)v − Tα (t)vk + kTα (t)v − vk −−→ 0. want to show A e Take v ∈ D(A). So we have Z t T (t)v − v = T (s)Av ds. This follows since for any  > 0 by (34) we can choose α0 > 0 such that kT (t)v − Tα0 (t)vk ≤  2 for t ∈ [0. Now recall from Theorem 2 part (b) that t Z Tα (t)v − v = Tα (s)Aa v ds 0 and Z lim Tα (t)v − v = T (t)v − v. e denote the infinitesimal generator of T (t). Tα (t)Aα v → T (t)Av uniformly on compact t intervals. Let A e = A.e. we want to show that lim kT (t)v − vk = 0. Tα (s)Aa v ds = 0 where the last limit and integral can be interchanged due to the uniform convergence. α→∞ lim α→∞ t Z 0 t T (s)Av ds for v ∈ D(A).

0 As in the proof of Theorem 6 we can show e = v. e I(α)(σI − A)v This implies e for α ∈ ρ(A). Springer-Verlag. Linear Operators. New York: Springer-Verlag. III Interscience. Kato. Therefore. (1963). by Theorem 2. e I(α) = Rα (A) By this and (38) we have e and A = A. D(A) ⊂ D(A) A) e e e (αI − A)D(A) = (αI − A)D( A) (38) e on D(A). 1971. ∀ v ∈ D(A). Therefore. [3] Yoshida. v ∈ D(A) e = A. Vols. II. 1966.Y.Dunford and J. e D(A) = D(A) 2 References [1] T. If α > ω then α ∈ ρ(A) which implies that (αI − A)D(A) = X. K. N. [2] N. since A = A Recall (37) so that for α > ω we have Z I(α) ≡ t e−αt T (t) dt exists. Functional Analysis and Its Applications.and we have T (t)v − v 1 lim = lim t→0 t→0 t t Z t T (s)Av ds = Av 0 e and Av e = Av. I. Schwartz. 18 . But Next we show the A e and A e extends A which implies that (αI − A)D( e e = X. Perturbation Theory of Linear Operators.